2010
DOI: 10.1097/scs.0b013e3181d7f0c5
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Melanotic Neuroectodermal Tumor of Infancy Treated Conservatively With Enucleation

Abstract: Melanotic neuroectodermal tumor of infancy (MNTI) is an uncommon, rapidly growing neoplasm of neural crest origin that primarily develops in the maxilla of infants during their first year of life. Mandibular lesions are rare and account for about 6% of all cases. Radical surgical excision is usually curative, but patients should be followed up closely because recurrence may occur in approximately 10% to 20% of cases. In this study, we report a case of mandibular MNTI in a 4-month-old male patient that was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…Melanotic neuroectodermal tumor of infancy may share a common histological and immunophenotypic expression with other lesions, such as cellular blue nevus, melanoma, neuroblastoma, and rhabdomyosarcoma, but MNTI commonly does not express diffuse reactivity with S-100, ( 2 , 3 , 6 , 8 ) as observed in our case. Other markers, such as HMB45, Melan A, cytokeratin, and neuroblastic markers, such as synaptophysin and neuron-specific enolase, can help with the diagnosis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Melanotic neuroectodermal tumor of infancy may share a common histological and immunophenotypic expression with other lesions, such as cellular blue nevus, melanoma, neuroblastoma, and rhabdomyosarcoma, but MNTI commonly does not express diffuse reactivity with S-100, ( 2 , 3 , 6 , 8 ) as observed in our case. Other markers, such as HMB45, Melan A, cytokeratin, and neuroblastic markers, such as synaptophysin and neuron-specific enolase, can help with the diagnosis.…”
Section: Discussionsupporting
confidence: 60%
“…This treatment modality is curative when tumors are easily detached from the bone, as in this case. ( 8 ) Moreover, esthetic sequelae and alteration in normal face development may be prevented by this conservative surgical approach. ( 10 ) Rachidi et al, ( 4 ) reported that recurrence usually occurs within 6 months after treatment and in patients younger than 4.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence may occur due to invasion of the tumor edge into the bone, difficulty in complete resection due to a tumor with no envelope ( 15 ) or multicenter growth. In previous studies, high recurrence rates and no recurrence despite incomplete resection have been reported ( 16 ). The lack of recurrence without complete resection may stem from a compaction effect that triggers an immune response to destroy the remaining tumor cells.…”
Section: Discussionmentioning
confidence: 97%
“…В мировой литературе описано около 500 случаев МНЭО [1]. Встречается преимущественно у детей первого года жизни, возрастной пик заболевания -5 месяцев [2]. У 7 % больных могут определяться отдаленные метастазы [3].…”
Section: Introductionunclassified